Penerapan Sistem Manajemen Arsip Elektronik Dalam Meningkatkan Efisiensi Persuratan Organisasi - Darmansah, T; Sani, Dinda Aulia; Munawwarah, Tarisa; Kholizah, Nur Alfiana; Hanifah, Fathia (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
In archive management, a system implemented to manage letter archives is a very good thing. In the 5.0 era, the use of electronics is commonplace, even a necessity. The use of electronics in records management increases the efficiency of correspondence. In this research, which uses the research method, the author intends to explain the application of a system that can be used in archive management and matters related to it. An example that can be adopted is the use of an application that makes the process of preparing letters from start to finish easier, this shows efficiency in archiving letters.